Gluten-Free Snacks Based on Brown Rice and Amaranth Flour with Incorporation of Cactus Pear Peel Powder: Physical, Nutritional, and Sensorial Properties - Dayanne Vigo Miranda; Meliza Lindsay Rojas; Sandra Pagador; Leslie Lescano; Jesús Sanchez-Gonzalez; Guillermo Linares (International Journal of Food Science)
An agroindustrial by-product (cactus pear peel) and whole grains flour (brown rice and amaranth) were used to present a gluten-free snack proposal. The effect of 5% (F1), 7% (F2), and 10% (F3) substitution of brown-rice flour for yellow cactus pear peel powder (Opuntia ficus-indica) on the snack physical, sensorial, and nutritional properties was evaluated. In addition, 20% of amaranth flour (Amaranthus caudatus) was used for all formulations. As the percentage of substitution increased, the a⁎ value increased, while the L⁎ decreased. The control snacks presented higher hardness, while the snacks with 10% substitution presented a greater crispness. The sensorial properties (overall liking, colour, crispness, and oiliness) reported that the samples containing cactus pear peel powder were the most accepted. The fat content decreased as the substitution percentage increased. The F3 formulation presented the best physical and sensorial properties and when compared with other commercial snack brands, it presented low fat and an adequate protein and fibre content. Therefore, snacks based on brown rice, amaranth, and cactus pear by-product could be considered as a good option of gluten-free product, contributing to reducing the lack of gluten-free products on the markets.